The IMF crisis of 1976 and British politics - Hickson, Kevin (Tauris Academic Studies, 2005)
The IMF crisis of 1976 was a seminal event in British political history, with the government seen as going 'cap in hand' to the International Monetary Fund in order to avert financial meltdown. This text uses original source material in order to identify the economic thought and practice which caused the crisis.
Includes bibliographical references (p. [239]-253) and index
Keywords: International Monetary Fund; Internationaler Währungsfonds; Geschichte 1976-1977; Economische crises; Financiële crises; IMF; Politik; Wirtschaftspolitik; Monetary policy -- Great Britain; Financial crises -- Great Britain; Finanzpolitik; Krise; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland; Großbritannien; Great Britain -- Politics and government -- 1964-1979; Great Britain -- Economic policy -- 1964-1979